2016
DOI: 10.3390/f7030059
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Drying Strains between Tangential and Radial Directions in Asian White Birch

Abstract: Abstract:In this study, wood disks of 30 mm in thickness cut from white birch (Betula platyphylla Suk) logs were dried at a constant temperature (40˝C). The drying strains including practical shrinkage strain, elastic strain, viscoelastic creep strain and mechano-sorptive creep were measured both tangentially and radially. The effects of moisture content and radial position on each strain were also discussed qualitatively. Overall, the difference of the practical shrinkage strain between the tangential and rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…These results confirmed the MC effect under loading on MS strains. The same conclusion was reported by Rice and Youngs (1990) and Fu et al (2016), who confirmed that MS strain is a function of moisture change and increases with decreased moisture content. Table 2 shows the MS strain results and mechano-sorption coefficient (m) for each perpendicular direction measured and load level.…”
supporting
confidence: 76%
“…These results confirmed the MC effect under loading on MS strains. The same conclusion was reported by Rice and Youngs (1990) and Fu et al (2016), who confirmed that MS strain is a function of moisture change and increases with decreased moisture content. Table 2 shows the MS strain results and mechano-sorption coefficient (m) for each perpendicular direction measured and load level.…”
supporting
confidence: 76%
“…Cutting wood log into thin disks is an advantageous to better understand the evolution of drying stresses because of the possibility to compare drying strains between tangential and radial directions [28]. Shrinkage ratio is an important parameter that can be used to characterize the performance of wood drying.…”
Section: Bd and Transverse Shrinkagementioning
confidence: 99%
“…During drying, shrinkage varied in different parts of the specimen due to the non-uniform distribution of MC and the differences in grain direction. For wood discs, the shrinkage in the tangential direction was restrained by the radial direction, and the shrinkage in lower MC parts was retrained by the higher MC parts (Fu et al 2016b). Therefore, the shrinkage strain was not just induced by only the loss of MC, but also due to the restrained drying stresses.…”
Section: Effect Of Pre-steaming On Restrained Shrinkage Strain and Frmentioning
confidence: 99%